On implications of micro price data for macro models - Bartosz Maćkowiak; Frank Smets (European Central Bank (ECB), 2008)
We review the recent literature that studies new, detailed micro data on prices. We discuss implications of the new micro data for macro models. We argue that the new micro data are helpful for macro models, but not decisive. There is no simple mapping from the frequency of price changes in micro data to impulse responses of prices and quantities to shocks. We discuss ideas that promise to deliver macro models matching the impulse responses seen in macro data while being broadly in line with micro data.
Keywords: E3; E5; 330; micro price data; models of price setting; real effects of nominal shocks; sticky prices; Preismanagement; Preisrigidität; Schock; Makroökonomik; Theorie